Giant Cervicothoracic Cystic Lymphangioma in a Neonate: Clinical Challenges and Management Considerations - Bustamante-Ordoñez, Marina A.; Curi-Vilchez, Gianelli S.; Marchand-Bayona, Eduardo; Zavaleta-Corvera, Carlos; Samanez-Obeso, Angel (American Journal of Perinatology Reports, 2025)
Lymphangiomas are benign vascular malformations of the lymphatic system, commonly affecting the head and neck. Neonatal cases pose significant clinical and surgical challenges.We report a premature female neonate (35 weeks of gestation) with a large cervicothoracic cystic lymphangioma (8 × 7 cm), causing respiratory distress and vascular compression. Imaging revealed an extensive lymphatic malformation (160 × 67 × 87 mm), affecting the sternocleidomastoid muscle, salivary glands, and adjacent vasculature. Surgical resection achieved 90% tumor removal while preserving neurovascular structures. Postoperative complications included transient neuromotor deficit of the right upper limb and Candida lusitaniae sepsis. Despite intensive care, tumor progression led to respiratory failure, and the patient succumbed 12 days' postsurgery.Extensive cervicothoracic lymphangiomas in neonates require complex management. Imaging aids in surgical planning, delineating tumor extent, and complications. While surgical resection is the standard treatment, it carries risks in neonates with large lesions. Sclerotherapy has shown efficacy in macrocystic lymphangiomas but remains debated for extensive neonatal cases. A multidisciplinary approach is crucial to optimize outcomes.Neonatal cervicothoracic lymphangiomas pose significant challenges. Surgery remains primary, but sclerotherapy may be considered in selected cases. Multidisciplinary management is essential to improve prognosis and reduce morbidity.
Keywords: lymphangioma; lymphatic malformations; sclerotherapy; surgical complications